Comparative human resource management in the European banking sector: The effect of collective bargaining power on working conditions - Ines Blohm; Sebastien Briel; Claudia Brülin; Uta Heumann; Martina Pauly (Luxembourg Income Study (LIS), 2006)
The purpose of this paper is to examine the influence of trade unions' bargaining power on the outcome of bargaining negotiations. It is expected that higher bargaining power leads to better bargaining outcomes such as higher wages and fewer working hours. As bargaining power is a construct that is difficult to measure it will be operationalised by three indicators: union density, bargaining coverage and workers on strike. After having conducted a regression analysis it can be said that the hypothesis does not hold without restrictions. A detailed interpretation of the results will be given in this paper and a conclusion with suggestions for further research will be drawn.
Keywords: 330; Mitbestimmung; Gewerkschaftsmitgliedschaft; Arbeitsbedingungen; Gewerkschaftspolitik; Personalmanagement; Bank; Schätzung; Europa